2016
DOI: 10.1101/094037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-induced formation of cell wall-deficient cells in filamentous actinomycetes

Abstract: The cell wall is a shape-defining structure that envelopes almost all bacteria. One of its main functions is to serve as a protection barrier to environmental stresses. Bacteria can be forced in a cell wall-deficient state under highly specialized conditions, which are invariably aimed at interrupting cell wall synthesis. Therefore, the relevance of such cells has remained obscure. Here we show that many filamentous actinomycetes have a natural ability to generate a new, cell wall-deficient cell type in respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…The activation of transposases are typically stimulated by stressful conditions, such as radiation, oxidative stress, temperature or inhibitory concentrations of metals and antibiotics (Vandecraen et al 2017). It was recently demonstrated that elevated levels of osmolytes induces hyperosmotic stress (Fuchino et al 2017;Ramijan et al 2018), which are conditions that are also used during preparation of protoplasts. This stress could also stimulate transposition events and consequent chromosomal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of transposases are typically stimulated by stressful conditions, such as radiation, oxidative stress, temperature or inhibitory concentrations of metals and antibiotics (Vandecraen et al 2017). It was recently demonstrated that elevated levels of osmolytes induces hyperosmotic stress (Fuchino et al 2017;Ramijan et al 2018), which are conditions that are also used during preparation of protoplasts. This stress could also stimulate transposition events and consequent chromosomal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…For Pulsed-Field Gel Electrophoresis (PFGE), 10 6 spores ml -1 of K. viridifaciens were inoculated in 25 ml of TSBS with 0.5% glycine or LPB (Ramijan et al 2018). Cultures were grown at 30°C agitating at 200 rpm for 16 and 40 h, respectively.…”
Section: Pulsed-field Gel Electrophoresismentioning
confidence: 99%
“…The activation of transposases are typically stimulated by stressful conditions, such as radiation, oxidative stress, temperature or inhibitory concentrations of metals and antibiotics [38]. It was recently demonstrated that elevated levels of osmolytes induces hyperosmotic stress [25, 39], which are conditions that are also used during preparation of protoplasts. This stress could also stimulate transposition events and consequent chromosomal rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea is that other cell wall-deficient cells, called L-forms, which have likewise been exposed to osmotic stress conditions, carry chromosomal lesions. In this context it is interesting to note that in three independent L-form lineages of K. viridifaciens lesions in the right chromosomal arms were found in addition to loss of KVP1 [25]. These three strains retained a similar region of KVP1 in their genomes, with a size of 164,773 bp for alpha and M1, and 164,642 bp for M2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation